(untitled) (Biological Sciences - PJSIR, 2004)
A comparative ecological survey of phytoplankton part II of Lake Bakar, district Sanghar and Lake Phoosna, district Badin was carried out during August, 1993 to July, 1996. A total of 122 species belonging to 45 genera of 15 families of 5 orders of class Chlorophyceae were recorded. 11 species were common in both Lakes. 94 species were present in Lake Bakar and 17 in Lake Phoosna. The study showed that the aquatic environment of Lake Bakar is qualitatively much better as compared to Lake Phoosna.